Penerapan Media Webquest Berbasis Google Sites dalam Pembelajaran Masa Pandemi Covid-19 di MI Bilingual Roudlotul Jannah Sidoarjo - Arindra Evandian Bhagaskara; Aulia Kaffah Firdausi; Mochammad Syaifuddin (Jurnal Bidang Pendidikan Dasar, 2021)
This research will discuss about the application of webquest media based on googe sites for online learning in low class classes as well as examining the strengths and weaknesses of implementing this media.. Qualitative research is the type of research chosen in conducting research on how the webquest media is applied. Data collection using interviews, observation, and documentation. Data analysis techniques start from data reduction, data presentation, and conclusions. The conclusion from the results of this study is the webquest media can be applied as an alternative to implementing distance learning by utilizing google sites. The advantage of the googe sites based webquest media is that it can increase interest in learning and develop students' scientific attitudes. The weakness of the googe sites based webquest media lies in the differences in the creativity of teachers in making media and the barriers for students who have less reading skills.